Bibliometric Analysis and Visualization of Energy Economics and Policy in Scopus from 2010 to 2021 - Muhtar, Entang Adhy; Rusli, Budiman; Karlina, Nina; Candradewini, Candradewini; Muharam, Riki Satia (International Journal of Energy Economics and Policy, 2021)
The aim of this study was to analyse the bibliographic characteristics and content of articles on energy economics and policy published in journals indexed by Scopus written by researchers from throughout the world from 2010 to 2021. We conducted a bibliometric and content analysis of publication in the Scopus database. We only retrieved articles written in English. We conducted content analysis using the VOSviewer software and visualized the co-occurrence of keywords and bibliographic coupling of sources and countries. Following the study protocol, we found 838 articles on energy economics and policy over the past 11 years. The most productive journal that published these articles was Journal of Cleaner Production (n = 100). The post productive country was the United Kingdom (n = 353). Based on cititations, the most influential authors were O. Ozel (n = 878). The keywords of research on energy economics and policy 8 clusters (e.g policy, energy policy, energy, china, analysis, impact, renewable energy policy and development). From a global perspective, energy economics and policy research in the past one decades has increased significantly. There were United Kingdom published journals ominated publications. Thus, Asian country need to conduct more active research on this topic. Keywords: Bibliometric; Energy; Economics; Policy JEL Classifications: B10, H00, H11, N10, O10 DOI: https://doi.org/10.32479/ijeep.11848